The revival of 1857-58 : interpreting an American religious awakening - Long, Kathryn, 1950- (New York : Oxford University Press, 1998)
This book provides a fresh, in-depth examination of the Revival of 1857-58, a widespread religious awakening most famous for urban prayer meetings in major metropolitan centers across the United States. Often mentioned in religious history texts and articles but overshadowed by scholarly attention to the first and second "Great Awakenings," the revival has lacked a critical, book-length analysis. This study will help to fill this gap and to place the event within the context of Protestant revival traditions in America. The book combines insights from contemporary scholarship concerning revivals, women's history, and nineteenth-century mass print with extensive primary source research.
"Prayer-meetings--in all parts of the land" : the revival takes shape as history -- "Affording public amusement--[and] gratifying the curiousity" : revivalism in the news -- The influence of family, church, and association : personal perspectives on the revival -- A "desire--that the ladies would keep away" : gender tensions and the masculinization of urban piety -- "Great revival" or "great reformation"? : the privatization of northern revivalism -- "Where is the evidence of your revival of religion?" : critiques of the revival's social impact -- Legacies of 1857-58 : D.L. Moody and the "revival generation."
"The Frank S. and Elizabeth D. Brewer prize essay of the American Society of Church History."
Includes bibliographical references (pages 121-239) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Prayer Meeting Revival (1857-1858); United States -- Church history -- 19th century; Réveil de 1857-1858.; États-Unis -- Histoire religieuse -- 19e siècle.; RELIGION -- Christianity -- History; United States; Opwekkingsbewegingen; Amerika; 11.59 church history, history of doctrine: other; Réveils (religion) -- États-Unis -- Histoire -- 19e siècle.; États-Unis -- Histoire religieuse -- 19e siècle.; 1800-1899; Electronic book; Church history